Bcl-2, Bcl-x(L), and Bcl-w are not equivalent targets of ABT-737 and navitoclax (ABT-263) in lymphoid and leukemic cells - Mérino, Delphine (American Society of Hematology, 2012)
The BH3-mimetic ABT-737 and an orally bioavailable compound of the same class, navitoclax (ABT-263), have shown promising antitumor efficacy in preclinical and early clinical studies. Although both drugs avidly bind Bcl-2, Bcl-x(L), and Bcl-w in vitro, we find that Bcl-2 is the critical target in vivo, suggesting that patients with tumors overexpressing Bcl-2 will probably benefit. In human non-Hodgkin lymphomas, high expression of Bcl-2 but not Bcl-x(L) predicted sensitivity to ABT-263. Moreover, we show that increasing Bcl-2 sensitized normal and transformed lymphoid cells to ABT-737 by elevating proapoptotic Bim. In striking contrast, increasing Bcl-x(L) or Bcl-w conferred robust resistance to ABT-737, despite also increasing Bim. Cell-based protein redistribution assays unexpectedly revealed that ABT-737 disrupts Bcl-2/Bim complexes more readily than Bcl-x(L)/Bim or Bcl-w/Bim complexes. These results have profound implications for how BH3-mimetics induce apoptosis and how the use of these compounds can be optimized for treating lymphoid malignancies.